Restructuring in the banking industry with implications for Europe - Arnoud W. A. Boot (EIB Papers, 2003)
Set against the background of a rapidly consolidating financial sector, this paper explores the main forces that are driving this process. Acknowledging that the search for scale and scope economies is one of them, the paper emphasises that the empirical evidence in support of such economies is mixed, at best; while scale and scope economies exist, in principle, they are difficult to attain in practice. The paper considers strategic positioning in an uncertain and rapidly changing environment a more important factor: by expanding scope (and scale), financial institutions acquire options to venture into new activities. An implication of this strategic-option explanation is that consolidation, scope expansion in particular, will partially unravel as and when uncertainty declines and competition forces financial institutions to discover their true competitive advantages.
Keywords: 330; Bank; Industrieller Strukturwandel; Reorganisation; EU-Staaten